The great pyramids of America: A revised history of U.S. business groups, corporate ownership, and regulation, 1926–1950. (29th December 2018) - Kandel, Eugene; Kosenko, Konstantin; Morck, Randall; Yafeh, Yishay
Abstract : Research Summary : Control‐magnifying (pyramidal) business groups—multiple tiers of partially‐owned listed affiliates and fully‐owned private affiliates, a dominant organizational form around the world—are virtually absent in America today. Using newly‐assembled historical data, we show that such groups were ubiquitous in the U.S. economy in the 1930s. They came under attack because of their economic and political sway: Some New Deal reforms—proscriptions against public utilities pyramids, intercorporate dividend taxes, and rules governing investment companies—were explicitly aimed at deterring existing groups and preventing new ones from forming. Others, for example, estate taxes and securities law reforms, may have also worked against them. No single reform triggered the immediate dissolution of groups; they broke up under an ongoing anti‐big business sentiment. These events offer lessons for policymakers today. Managerial Summary : Most listed U.S. firms are "standalone"—they do not control, and are not controlled by, other listed firms. Control‐magnifying (pyramidal) business groups—multiple tiers of partially‐owned listed affiliates and fully‐owned private affiliates (e.g., Samsung or Tata)—are ubiquitous around the world but virtually absent in United States. In such groups, the combination of multiple tiers and partial ownership enables control over vast corporate empires. Using newly‐assembled historical data, we show that the U.S. corporate ownership as we know it today is a recent phenomenon: pyramidal groups were common in United States of the 1930s. President Roosevelt, who regarded their economic and political power as excessive, initiated a sequence of reforms which appears to have worn these groups down and probably also kept new ones from forming.JEL CLASSIFICATION : G3, G34, G38, N22.